Measurement of electron neutrino and antineutrino cross sections at low momentum transfer - Henry, S.; Su, H.; Akhter, S.; Ahmad Dar, Z.; Ansari, V.; Ascencio-Sosa, M.V.; Athar, M.; Bashyal, A.; Betancourt, M.; Bonilla, J.L.; Bravar, A.; Díaz, G.A.; et al. (American Physical Society, 2024)
Accelerator based neutrino oscillation experiments seek to measure the relative number of electron and muon (anti)neutrinos at different L=E values. However high statistics studies of neutrino interactions are almost exclusively measured using muon (anti)neutrinos since the dominant flavor of neutrinos produced by accelerator based beams are of the muon type. This work reports new measurements of electron (anti)neutrinos interactions in hydrocarbon, obtained by strongly suppressing backgrounds initiated by muon flavor (anti)neutrinos. Double differential cross sections as a function of visible energy transfer, Eavail, and transverse momentum transfer, Pᴛ, or three momentum transfer, q₃ are presented.
Keywords: Neutrino; Muon; Physics; Particle physics; Electron neutrino; Nuclear physics; Neutrino oscillation; Momentum transfer; Electron; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.00